A Randomized, Controlled Trial of Mirror Therapy for Upper Extremity Phantom Limb Pain in Male Amputees - Finn, Sacha B.; Perry, Briana N.; Clasing, Jay E.; Walters, Lisa S.; Jarzombek, Sandra L.; Curran, Sean; Rouhanian, Minoo; Keszler, Mary S.; Hussey-Andersen, Lindsay K.; Weeks, Sharon R.; Pasquina, Paul F.; Tsao, Jack W. (Frontiers in Neurology, 2017)
Objective: Phantom limb pain is prevalent in patients post-amputation and is difficult to treat. We assessed the efficacy of mirror therapy in relieving phantom limb pain in unilateral, upper extremity male amputees. Methods: Fifteen participants from Walter Reed and Brooke Army Medical Centers were randomly assigned to one of two groups: mirror therapy (n=9) or control (n=6, covered mirror or mental visualization therapy). Participants were asked to perform 15 minutes of their assigned therapy daily for 5 days/week for four weeks. The primary outcome was pain as measured using a 100-mm Visual Analogue Scale (VAS). Results: Subjects in the mirror therapy group had a significant decrease in pain scores, from a mean of 44.1 (SD=17.0) to 27.5 (SD=17.2) mm (p=0.002). In addition, there was a significant decrease in daily time experiencing pain, from a mean of 1022 (SD=673) to 448 (SD=565) minutes (p=0.003). In contrast, the control group had neither diminished pain (p=0.65) nor decreased overall time experiencing pain (p=0.49). A pain decrement response seen by the tenth treatment session was predictive of final efficacy. Conclusions: These results confirm that mirror therapy is an effective therapy for phantom limb pain in unilateral, upper extremity male amputees, reducing both severity and duration of daily episodes.